2017
DOI: 10.1101/171306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRuML: A Translator for Rule-Based Modeling Languages

Abstract: Rule-based modeling languages, such as the Kappa and BioNetGen languages (BNGL), are powerful frameworks for modeling the dynamics of complex biochemical reaction networks. Each language is distributed with a distinct software suite and modelers may wish to take advantage of both toolsets. This paper introduces a practical application called TRuML that translates models written in either Kappa or BNGL into the other language. While similar in many respects, key di erences between the two languages makes transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…to obtain the reaction product (Faeder et al, 2005(Faeder et al, , 2009. The authors' comparison of the time traces of Kappa-and BNGL-defined rules shows equivalent results under stochastic realisations (Suderman and Hlavacek, 2017). An earlier study by Suderman and Deeds (2013) also showed equality of results between both frameworks.…”
Section: Discrepancies In Dynamics Between Modelsmentioning
confidence: 89%
See 2 more Smart Citations
“…to obtain the reaction product (Faeder et al, 2005(Faeder et al, , 2009. The authors' comparison of the time traces of Kappa-and BNGL-defined rules shows equivalent results under stochastic realisations (Suderman and Hlavacek, 2017). An earlier study by Suderman and Deeds (2013) also showed equality of results between both frameworks.…”
Section: Discrepancies In Dynamics Between Modelsmentioning
confidence: 89%
“…of Kappa-and BNGL-defined rules shows equivalent results under stochastic realisations (Suderman and Hlavacek, 2017). An earlier study by Suderman and Deeds (2013) also showed equality of results between both frameworks.…”
Section: /23mentioning
confidence: 94%
See 1 more Smart Citation
“…Features or conventions present in the modeling language, such as those described in this section, can result in language-specific behaviors. This is especially evident when attempting to translate a model into a different rule-based modeling language (Suderman and Hlavacek, 2017). Documentation of pathological cases (both for the modeling language and the simulation engine) as well as the semantics of the rule-based modeling language are essential for accurate and consistent modeling and simulation.…”
Section: Identical Site Pathologiesmentioning
confidence: 99%
“…Other model standards may be indirectly supported by converting to BNGL or SBML. For example, rule-based models defined in the Kappa language [46,47] can be converted to BNGL using the software tool TRuML [48].…”
Section: Introductionmentioning
confidence: 99%